دور محاسبة الأجور في الإفصاح المحاسبي لمصاريف العمال دراسة حالة: شركة كوسيدار للبناء مشروع مستشفى الأم والطفل حي 8 ماي -الوادي - علي بلي; البشير بن عمر; عبد الجواد مرابط (جامعة الوادي eloued of university, 2025)
"يهدف هذا البحث إلى إبراز دور محاسبة الأجور في الإفصاح المحاسبي لمصاريف العمال، باعتبارها من العناصر الأساسية في التقارير المالية للمؤسسات. وقد اعتمدنا في إعداد هذه الدراسة على المنهج الوصفي التحليلي، بالاستناد إلى مجموعة من المراجع المتنوعة مثل الكتب، والمجلات العلمية، والمقالات، والمذكرات، بالإضافة إلى نصوص قانونية ذات صلة بالموضوع. حيث تم تقسيم البحث إلى فصلين: قسم نظري تناولنا فيه المفاهيم الأساسية المتعلقة بمحاسبة الأجور والإفصاح المحاسبي، وقسم تطبيقي خصصناه لدراسة حالة ميدانية بشركة كوسيدار للبناء، من خلال كشف رواتب لعينات في الشركة. This study aims to highlight the role of wage accounting in the financial disclosure of employee expenses, considering it one of the key elements in the financial reports of institutions. The descriptive-analytical method was adopted in conducting this research, relying on various references such as books, scientific journals, articles, dissertations, and relevant legal texts. The research was divided into two main parts: a theoretical section, in which we discussed the fundamental concepts related to wage accounting and financial disclosure, and a practical section, where we conducted a case study on Cosider Construction Company, Through salary disclosure for samples in the institution.
ماستر مالية وحاسبية
Keywords: محاسبة أجور، إفصاح محاسبي، مصاريف عمال، كشف راتب، مؤسسات اقتصادية.; Wage Accounting; Salary Statement; Financial Disclosure; Employee Expenses; Economic Institutions.